Rethinking Revisionism in World Politics. (30th March 2021) - He, Kai; Feng, Huiyun; Chan, Steve; Hu, Weixing
Abstract: Revisionism is an important concept in international relations discourse, and it is especially prevalent in discussions about relations between China and the United States in the context of a possible power transition. Yet, this concept has until recently not received the systematic research attention that it deserves. We present in this essay different strategies that a revisionist state may pursue. It builds on recent scholarship by other colleagues and is drawn from a larger project of ours to study revisionism historically and develop it conceptually. We argue that military conquest and subversion—or in our terminology, hard revisionism—have become less likely in today's world compared to the past. Instead, different approaches of soft revisionism intended to advance institutional changes should be given more attention. We provide a typology of these soft revisionist strategies and offer examples from recent Chinese and US conduct to illustrate them.